2022
DOI: 10.1002/brb3.2702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of toxic apolipoprotein E fragments on Tau phosphorylation and cognitive impairment in neonatal mice under sevoflurane anesthesia

Abstract: Background Anesthesia induces Tau phosphorylation and cognitive impairment in young, but not adult, mice. Apolipoprotein E (ApoE) may play a protective role in neuronal activity and injury repair, whereas its toxic fragments are reported to induce neurodegeneration and neurocognitive impairment in patients with Alzheimer's disease (AD). Therefore, we set out to test the hypothesis that the difference in ApoE fragments, but not the full‐length ApoE, contributes to the difference in Tau phosphorylation and neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Based on previous research (7)(8)(9)(10)(11), we discovered that newborn mice exhibit neurotoxicity after multiple exposures to sevoflurane anesthesia. In the current study, we employed quantitative proteomic analysis using TMTpro(16-plek) tagging and LC-MS/MS to identify 443 DEPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous research (7)(8)(9)(10)(11), we discovered that newborn mice exhibit neurotoxicity after multiple exposures to sevoflurane anesthesia. In the current study, we employed quantitative proteomic analysis using TMTpro(16-plek) tagging and LC-MS/MS to identify 443 DEPs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that repeated or long-term sevoflurane exposure prior to 3-4 years of age can increase the potential for future learning and memory challenges (3)(4)(5), although available data remain debatable (6). Furthermore, our previous studies have demonstrated that multiple exposures to inhalational anesthetics, such as sevoflurane, can cause adverse effects, including neuroinflammation, apoptosis, synaptic insufficiency, and cognitive deficits in 6-day-old newborn mice, while 60-day-old adult mice showed no notable damage (7)(8)(9)(10)(11). The mechanisms underlying these age-dependent effects remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The role of this apoE truncated fragment to enhance tau phosphorylation was documented by studies showing that transgenic expression of apoE(Δ272–299) in mice caused tau hyperphosphorylation, preneurofibrillary tangle formation, learning and memory impairment, and early death [ 158 ]. Moreover, this C-terminal truncated apoE fragment was not detected in mice expressing apoE2, where tau phosphorylation and cognitive impairment were also found to be reduced [ 159 ]. Whether differences in susceptibility of apoE2 and apoE4 to intraneuronal proteolysis is due to conformational differences (as reviewed above in Section 2.1.1 ) need to be clarified.…”
Section: Role Of Apoe In Neurological Health and Diseasementioning
confidence: 99%
“…In addition, Tau is a microtubule-associated protein, and the hyperphosphorylated form of Tau is significantly increased after nerve injury ( 60 ), so it is considered to be an important factor affecting general anesthetics leading to neurotoxicity and cognitive impairment in the newborn brain. ApoE toxic fragment may be one of the potential mechanisms of neuronal Tau phosphorylation in neonatal mice exposed to sevoflurane ( 61 ). Coenzyme Q10 may reduce ApoE and phosphorylated Tau expression, thereby attenuating sevoflurane-induced neuroinflammation in mouse hippocampal neurons of newborn mice ( 62 ).…”
Section: Molecular Proteinmentioning
confidence: 99%